(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article provides information about the types of forced labor used in practice in connection with agricultural work in the Turkestan region during the Uzbek khanates - shoemaking, hashar, etc. In particular, the conditions of shoemaking, factors calling for hashar, conditions and methods of organizing hashar are discussed in more detail.